Hang-up IUD, New Technique for Suturing CuT-380A IUD to Uterine Fundus in Immediate Postplacental Insertion during Cesarean Delivery: Twelve Months Follow up: Hang-up IUD, Teknik Baru Penjahitan IUD CuT-380A pada Fundus Uteri pada Insersi IUD Pascaplasenta Persalinan Bedah Sesar: Pemantauan Dua Belas Bulan - Hary Tjahjanto; Indah T Haryuni (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: The aim of this study was to evaluate the effectiveness,side effects and acceptability of postplacental CuT-380A IUD insertionusing new technique for suturing to uterine fundus during cesareansection (hang up technique). Method: Prospective cohort study of postplacental IUD CuT-380Ainsertion during cesarean delivery. Hang-up technique consists ofperforming a puncture in the center of the fundus wall using straightneedle into the uterine cavity and subsequently using chromic catgutno. 1 to tie the IUD using anchor knot and hanging the IUD to thefundus. Our subjects were women who underwent caesarean deliveryat dr. Kariadi Hospital between 1st June 2009 to 31st April 2011and followed up at <6 weeks, 6 weeks, 3 , 6, 9 and 12 months. Result: From 116 women, 8 women (7.4%) were lost to follow-up.The 108 women were observed by scheduled home visits or by mailor telephone. The youngest patient was 15 years old and the oldestwas 40 years old. The proportion of primiparous and multiparouswomen was comparable (49.1% and 50.9%), gestational age was28-44 weeks, birth weight ranged 2,950-4,500 grams. Six weekspost cesarean section, out of the 108 women, two women complainedof foul-smelling lochia, two had puerperal fever, and threecomplained of pelvic pain. At 6-months follow-up, 3 women underwentIUD removal because two found the string very disturbing andthe other wanted to get pregnant because their child died. At 9-months post-cesarean one woman was reported to be pregnant withIUD in situ. At >12 months follow-up, one woman underwent IUD removalbecause of severe dysmenorrhea. No perforation or expulsionwas reported. Conclusion: Immediate postplacental insertion of IUD CuT-380A usinghang-up technique is safe and effective. Typical use effectivenessis high (Pearl Index 0.93) and there were no reported incidents ofexpulsion or perforation. Acceptance and continuation rate werehigh, 98.15% and 95.37% respectively.Keywords: anchor knots, cesarean section, hang-up IUD, postplacentalIUD insertion